2007
DOI: 10.1007/s00425-007-0479-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies of xylan interactions and cross-linking to synthetic lignins formed by bulk and end-wise polymerization: a model study of lignin carbohydrate complex formation

Abstract: The mechanism of lignin carbohydrate complex formation by addition of polysaccharides on quinone methide (QM) generated during lignin polymerisation was investigated using a model approach. Dehydrogenation polymers (DHPs, lignin model compounds) were synthesized from coniferyl alcohol in the presence of a glucuronoarabinoxylan (GAX) extracted from oat spelts, by Zutropfverfahren (ZT) and Zulaufverfahren (ZL) methods. The methods ZT and ZL differed in their distribution of QM over the reaction period but genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 34 publications
4
63
0
Order By: Relevance
“…These polysaccharides are known to form chemical bonds with lignin to form lignin-carbohydrate complexes (Tenkanen et al, 1999;Lawoko et al, 2005;Barakat et al, 2007), and since hemicelluloses are deposited prior to or concurrently with lignin (Kim et al, 2010a(Kim et al, , 2010b(Kim et al, , 2010c(Kim et al, , 2011, the possibility that they influence lignin deposition seems reasonable. This study extends these earlier results by definitively colocalizing lignin and polysaccharides on the same field of view and measuring their association by image analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These polysaccharides are known to form chemical bonds with lignin to form lignin-carbohydrate complexes (Tenkanen et al, 1999;Lawoko et al, 2005;Barakat et al, 2007), and since hemicelluloses are deposited prior to or concurrently with lignin (Kim et al, 2010a(Kim et al, , 2010b(Kim et al, , 2010c(Kim et al, , 2011, the possibility that they influence lignin deposition seems reasonable. This study extends these earlier results by definitively colocalizing lignin and polysaccharides on the same field of view and measuring their association by image analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of different polysaccharides, Iwata et al (1998) found that beech (Fagus sylvatica) glucomannans have the highest affinity for cellulose, followed by xyloglucan, xylan, and arabinogalactan. Mannans may also associate with xylans and with lignin (Lawoko et al, 2005;Barakat et al, 2007).…”
mentioning
confidence: 99%
“…Wheat straw lignin is known to contain arabinoxylans as the main carbohydrate impurities with lignin being linked with arabinose side chains of xylan by ether bonds (Sun et al, 1997). The majority of these ether linkages occur at the a-position of the propanoid chains of lignin as initially suggested by their possible cleavage under acidic conditions (Mc Donough, 1993;Cornu et al, 1994;Lawther et al, 1996) and later confirmed by NMR and xylanase-based fractionation (Barakat et al, 2007). Applying MW instead of CH decreased significantly the xylose content of the lignin but had almost no effect on the arabinose content.…”
Section: Characterization Of Extracted Ligninsmentioning
confidence: 96%
“…Dehydration enhances the local polysaccharide concentration and also reduces water attack on the quinone methide intermediate (Figure 4), enabling hemicellulose reactions to generate covalent benzyl esters and ethers of the LCCs (Figure 7). Consequently, the concentrations of lignin and LCCs probably track in the same direction [115]. Nucleation sites have been proposed for promoting lignin polymerization [28].…”
Section: Xylogenesismentioning
confidence: 98%
“…However, when 'Zulauf' technique was adopted, only noncovalent bonds were observed between xylan and DHP. The resulting xylan-DHP supramolecular nanocomposites were resistant to endoxylanase digestion [106,[113][114][115]. Uraki et al [116] reported that the hemicelluloses xylan and mannan adsorbed the monolignols non-covalently through hydrophobic forces.…”
Section: Mimicking Lccsmentioning
confidence: 99%